En recuerdo de un arqueólogo iraquí. Salah Salman Rumaiydh Ali al-Yuburi (1947-2017) - Córdoba, Joaquín María (ISIMU, 2019)
En recuerdo de un arqueólogo iraquí. Salah Salman Rumaiydh Ali al-Yuburi (1947-2017)